2015
DOI: 10.2495/safe150151
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for integrated early warning and disaster management in the UAE

Abstract: In the UAE, there are deficiencies in the use of technology in the exchange of information and reliance on the National Centre for Meteorology and Seismology Monitoring and Warning (NCMS). The new centre is affiliated to the Ministry of Presidential Affairs and it is established in coordination with concerned authorities. It is networked with similar centers in the region for the sharing of information and intervention at times of need. It also provides meteorology monitoring with advice and warning on storms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In this thesis, emphasis is given to the ICT point of view. Besides the four elements of the UNISDR framework, recent research showed that vulnerability aspects should also be considered by EWSs, such as environmental and social conditions, as well as economic and institutional capacities for dissemination and response [104,105].…”
Section: Early Warning Systemmentioning
confidence: 99%
“…In this thesis, emphasis is given to the ICT point of view. Besides the four elements of the UNISDR framework, recent research showed that vulnerability aspects should also be considered by EWSs, such as environmental and social conditions, as well as economic and institutional capacities for dissemination and response [104,105].…”
Section: Early Warning Systemmentioning
confidence: 99%